A Case Study Based Slope Stability Analysis at Chittagong City, Bangladesh - Farazi, Atikul Haque; Mia, Abu Jafor; Mahmud, Md. Ilias (UIR PRESS, 2018)
Heavy rainfall occurs almost every year in Bangladesh and induces landslides in the hilly regions of this country. Among them the Chittagong City has the worst scenario―as there lives a dense population, extending from the plain lands to the hilly area. So, for risk mitigation and management in this landslide prone city, slope safety margin should be determined. From this context, this article presents factor of safety (FS) values in terms of landslide hazard at Chittagong city, based on geotechnical parameters and slope geometry. Thus a preliminary idea on the allowable stress for slope design could be made from this study. In total, 16 hazard sites of the 2007 and 2008, rainfall induced, landslides were examined as a case study along with subsequent collection of in situ soil samples of the failed slopes for geotechnical laboratory analysis. For FS calculation, the limit equilibrium method for infinite slopes was deployed along with the Cousins’ stability chart. FS values from 0.94 to 1.57 were found at the hazard sites. The results imply that FS value more than 1.57 should be used for slope safety margin. Moreover, from a probabilistic approach, the authors recommend FS > 1.80 as optimum value for the region. Furthermore, a relationship between slope height to slope length ratio, or slope angle and FS was established for this region for a quick calibration of FS value by simple on-field measurement of slope parameters. It is expected that this scenario based finding would contribute in mitigation of landslide hazard risk at the study area. Additionally, site specific FS values were presented in a map by color indexing. This research could ascertain the location wise slope strength requirement and be considered as a guideline for future calculation for slope safety design against rainfall triggered landslides in this city.